A Rosa le encanta montar en su patineta = Rosa rides her scooter - Spanyol, Jessica; Canetti, Yanitzia (Swindon, UK : Child's Play (International) Ltd, 2021)
Unete a Rosa y sus amigos mientras juegan con sus scooters. Una serie importante que celebra la inclusion, promueve la igualdad de genero y abraza la singularidad de cada nino.
Join Rosa and her friends as they play with their scooters. An important series that celebrates inclusivity, promotes gender equality and embraces the uniqueness of every child.
On board pages = En paginas de carton duro.
Text in English and Spanish.
Keywords: Play -- Juvenile fiction; Friendship -- Juvenile fiction; Scooters -- Juvenile fiction; Spanish language materials -- Bilingual; Board books; Libros de carton